2014
DOI: 10.4081/optometry.2014.2164
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the practice of ocular self-medication in Cape Coast Metropolis, Ghana

Abstract: The purpose of the present study was to assess the practice of ocular self-medication among people of the Cape Coast Metropolis, Central Region of Ghana. A population-based survey involving 421 respondents ≥18 years old was conducted. A pre-tested interview-based questionnaire was used to collect data on demographics, ocular symptoms for which selfmedication was practiced, medical knowledge and self-care orientation. Households were systematically and randomly selected as study units. Analysis was done using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 19 publications
3
22
1
Order By: Relevance
“…is finding agrees with studies done in Ghana [6]. is might be due to the financial constraint that participants could not afford to pay all eye health services.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…is finding agrees with studies done in Ghana [6]. is might be due to the financial constraint that participants could not afford to pay all eye health services.…”
Section: Discussionsupporting
confidence: 91%
“…is was supported by different studies [2,6]. is might be due to the similarity of symptoms of eye diseases patients believing that ocular medications taken previously can cure their current eye disease.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Itching is typical of ocular allergy and diagnosis without the symptom of ocular itch is always problematic [10, 15, 21]. Studies have shown that bothersome nature of ocular itch is a major drive for the practice of ocular self medication not only among university students [43] but the general population [44]. Photophobia (26.2 %) was the least recognized symptom of ocular allergy as it associated with several other ocular diseases other than allergy [45].…”
Section: Discussionmentioning
confidence: 99%